The Effect of Bumper Stickers Strategy to Improve Students"™ Reading Comprehension Viewed from Students"™ Reading Interest - Saptarina, Eva; Sartika, Dewi; Amelia, Kiki Rizki (Journal of English Education Program, 2024)
Reading is essential for information acquisition, but students often struggle with understanding descriptive writing. To improve reading comprehension, educators could employ the Bumper Sticker strategy, using color-coded lists to help students grasp the text's main ideas. This study reports the effectiveness of the bumper sticker reading strategy in fostering students' reading interests. The quasi-experimental study comprised two groups of seventh-grade students, each consisting of 40 students. Data were gathered through a reading interest questionnaire and a multiple-choice reading comprehension test. Results reveal that the Bumper Sticker strategy effectively enhances reading comprehension aligned with students' interests. Notably, the conventional strategy also improves comprehension in alignment with students' interests. Lastly, the Bumper Sticker strategy is particularly effective for highly interested students. The recommendation is to employ the bumper sticker strategy, enabling students to create color-coded lists, thereby enhancing their comprehension of the material.